2017
DOI: 10.29252/johe.6.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Mental workload and affecting factors among firefighters in Tehran, Iran, in 2017

Abstract: Background: Firefighting and rescue require high physical and psychological needs under unpredictable and dangerous conditions. Thus, this study aimed to investigate mental workload and affecting factors in firefighters. Materials and Methods: This is a descriptive study which was conducted on 250 firefighters of Tehran, Iran. National Aeronautics and Space Administration Task Load Index (NASA-TLX) survey was used in order to evaluate the mental load among firefighters. This tool evaluates mental workload in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…As physical demand was the highest experienced by RIMS, followed by PPDA and EMRS, experts believed that firefighting is indeed a physically demanding job, and firefighters need to be physically fit to be capable of responding to emergency calls in no time 27,28 . The findings on mental demand which scored second-lowest contradicted previous research that reported cognitive load is more related to emergency responders' psychological behaviors 18 .…”
Section: Discussion Workload Demand Among Malaysian Firefighterscontrasting
confidence: 99%
See 4 more Smart Citations
“…As physical demand was the highest experienced by RIMS, followed by PPDA and EMRS, experts believed that firefighting is indeed a physically demanding job, and firefighters need to be physically fit to be capable of responding to emergency calls in no time 27,28 . The findings on mental demand which scored second-lowest contradicted previous research that reported cognitive load is more related to emergency responders' psychological behaviors 18 .…”
Section: Discussion Workload Demand Among Malaysian Firefighterscontrasting
confidence: 99%
“…Socio-demographic characteristics such as age, marital status, and working history had no significant impact on workload and job satisfaction 18 ; hence, this study shall also disregard socio-demographic characteristics correlation with workload level. The overall workload for all teams scored above 50, which is generally imposed toward the mid-to-high range of the NASA-TLX (Fig.…”
Section: Discussion Workload Demand Among Malaysian Firefightersmentioning
confidence: 99%
See 3 more Smart Citations